(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Hotel industry is considered to be one of the reputed industry in India. The study is to analyse the attitude of the respondents towards discounting offers and attractive package given by hotels and to find out the impact of Price complexity, discounting offers and attractive package towards selection of hotels. For this purpose a sample of 120 was collected from the respondents were percentage analysis, descriptive statistics, factor analysis, Kruskall wallis test, one way ANOVA and multiple regression were used as tools to analyse the data. The conclusion of the study is that price complexity has higher impact on price complexity than other variables taken for the study. It is also concluded that the quality of service has to be enhanced in future period of time based on packages designed and discounting factors.